Application of the Theory of Constraints to a production plant of natural juice and beverage concentrates - Villegas Montoya, Ana Gabriela (2016)
This research project was conducted in order to apply a model of continuous improvement to real situations. The company analyzed is a producer of concentrated juices and soft drinks. The goal of this project is to suggest improvements in the production process and the efficient management of resources, in order to minimize the current delays and failures of delivery orders that present the company as a problem. The methodology applied is the Theory of Constraints and the work is divided into six chapters. The first chapter contains a conceptual framework that provides the basis and a guideline in which the project has been developed. In the second chapter the general diagnosis has been made based on the current situation of the company, according to information gathered during visits and interviews. This assessment identified three root causes directly related to production constraints in the system. The chapter three develops the steps of the methodology with which it is possible to reduce the current problems of the plant and also to reduce the production time. Chapter four shows the results of the pilot test that was applied, taking into account the proposals presented in chapter three, and these results are presented with corresponding validations. On the other hand, chapter 5 presents the analysis of the proposal’s impacts. Finally in Chapter 6 the conclusions and recommendations are shown.